The influence of integrating Facebook group: Administrating and teaching English writing - Mortini, Asti Veto (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2019)
Writing is a basic skill which must be possessed by the students. This skill is needed in every teaching and learning process in English lesson. It is not only to express imagination in the written language but also to develop students’ creativity, thus, good teaching writing strategy is required to increase the students’ motivation to write. The objective of this research was to find out whether or not there was any significant influence on students’ writing narrative paragraphs achievements to the students of Senior High School 12 Palembang who are taught by integrating face book group and those who are not. Quasi experimental method was used in this research. One group experimental and one control groups were as samples. Data were collected through written tests; pretest and posttest and analyzed them using independent sample test. The result showed t-obtained was greater (13.906) than t-table (1.990) at the significance level p<0.05 with degree of freedom (df) = 56. It means that there was any significant influence on students’ writing narrative paragraphs achievements to the students of Senior High School 12 Palembang who are taught by integrating face book group and those who are not.